Study on Preparation Technology and Physical Fingerprint of Chuilian Jianpi Granules Based on QbD. (30th September 2021) - Zhou, Guangjiao; Li, Xiao-Wei; Li, Jin-Cai; Feng, Xue-Hua
Abstract : Objective . To optimize the preparation formula and technology of Chuilian Jianpi granules. Methods . The formulation and preparation process were optimized by single factor experiment and response surface analysis, with the molding rate, hygroscopicity, and fluidity of particles as the comprehensive evaluation indexes, and the comprehensive score as the response value according to different weights. To further evaluate the stability and feasibility of the preparation formulation and technology, the physical fingerprint of the granules was constructed by seven indicators including particle tap density, bulk density, hygroscopicity, water content, angle of repose, Hausner ratio, and relative homogeneity index. Results . The optimum formula conditions of Chuilian Jianpi granules were as follows: the dosage ratio of drug to adjuvant was 1 : 0.8, lactose:mannitol = 1.5 : 1, and the amount of wetting agent (90% ethanol) was 25% of the granules, with high-speed stirring granulation. The similarity of the physical fingerprints of the 10 batches of Chuilian Jianpi granules was high, which is above 98.5%. Conclusion . The optimized preparation technology was stable and feasible, which can provide reference for the development of Chuilian Jianpi granules and other Chinese medicine granules.